Effect of starting distance on vertical ground reaction forces in the normal dog - DuLaney, D.; Purinton, T.; Dookwah, H.; Budsberg, S. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
The purpose of this study was to evaluate the effect of starting distance on the peak vertical force (PVF) and associated vertical impulses (VI) of normal dogs. Five dogs of similar weight and body type were trotted at a velocity of 1.6–2.2 m/s from each of three starting distances; 2, 4, and 6 m, from the first plate in a two plate test field. A total of ten trials were recorded from each starting distance, five left first contacts and five right first contacts. Each ground reaction force (GRF) of interest was evaluated both within and between the three starting distances using a complete block ANOVA. There was not any significant effect of distance found on peak vertical forces in our study. However, distance did affect VI. Forelimb VI generated at a 2 m trot was significantly less than VI generated at a 6 m trot. Neither extreme distance was found to be significantly different than the 4 m VI. The VI of the hind limb was not significantly affected.
Keywords: Kinetics; gait analysis; vertical ground reaction forces; starting distance